Accuracy of ultrasonography and color Doppler in diagnosis of ovarian masses and its correlation with histopathological findings - Ghazal, Kariman; Hasan, Jihad El; Hijasi, Hanine; Koulaima, Ev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ovarian cancer is often diagnosed in advanced stages due to the absence of specific symptoms. Yet, there are no reliable screening tests for ovarian malignancies. However, improvements in imaging techniques such as ultrasonography and color Doppler increased the probability of early detection. The purpose of this study was to compare between the ultrasonographic and color Doppler findings of ovarian masses with their histopathological diagnosis. Methods: A retrospective review was performed on patients between January 2017 and January 2020 diagnosed to have an ovarian mass. The eligible patients were subsequently divided into 2 groups: group A included patients who had abdominal and vaginal ultrasound in order to assess the morphology of the ovarian neoformation, and group B included patients whose ovarian masses were evaluated by color Doppler in addition to transabdominal ultrasound in order to identify their vascularization as well as their morphology. Results: A total of 74 patients were included in the study with 42 patients in group A and 32 patients in group B. Of the 42 adnexal masses studied in group A, 8 (19.0%) were malignant, 33 (78.6%) were benign and 1 (2.4%) was borderline. Ultrasound had a sensitivity of 89.0%, a specificity of 100.0%, a positive predictive value (PPV) of 100.0%, a negative predictive value (NPV) of 97.0% and accuracy of 97.0%. On the other hand, of the 32 masses examined in Group B, 7 (21.9%) were malignant, 23 (71.9%) were benign and 2 (6.3%) were borderline. Color doppler had a sensitivity of 55.6%, a specificity of 95.5%, a PPV of 83.0%, a NPV of 84.0% and accuracy of 84.0%. When using color Doppler in addition to morphology score, the sensitivity was 100.0%, specificity 95.5%, PPV 90.0%, NPV 100.0% and accuracy 96.6%. Conclusions: Ultrasound combined to color Doppler improves the diagnosis of ovarian tumors with accurately detecting malignant from benign ones